De naam van de vrouw. - Rimbaut, Josiane (Gent : VC Geuzenhuis, 2011)
Agemans, Vroni ; Blancquaert, Lieve ; Braet, Hilde ; Breuer, Evi ; de Bruijne, Marianne ; De Meester, Nadine ; Eeckman, Franscine ; Germonprez, Paya ; Heyse, Krie ; Lauwaert, Yvette ; Martens, Sophie ; Pauwels, Marieke ; Roman, Saskia ; van Landuyt, Mi ; Van Lierde, Nadine ; Vermeersch, Vera ; Vandevelde, Julien
De naam van de vrouw, VC Geuzenhuis, Gent, 14 tot en met 22 mei 2011
boek